Wealth from Waste? Chinese Investments and Technology Transfer in the Tanzanian Plastic Recycling Industry - Ying Xia (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2019)
Since the 1990s, China has emerged as the center of the global waste trade and recycling industry, importing and reprocessing millions of tons of waste materials every year. In recent years, due to rising costs for labor and environmental compliance in China, Chinese investors have been exploring the recycling industry in Africa, currently serving both Chinese and African markets with a variety of products. This research examines the potential of knowledge transfer from Chinese investments in the Tanzanian plastic recycling industry to the local economy. It also assesses how the recent regulatory change in China, i.e., the imposition of an import ban on waste materials since 2018, has affected plastic recycling and reprocessing industries in Tanzania.
Keywords: 330